ANYAMAN PANDAN DI NAGARI PANINGGAHAN KECAMATAN JUNJUNG SIRIH KABUPATEN SOLOK - Desra Sanivo (HUMANITIS: Jurnal Homaniora, Sosial dan Bisnis, 2023)
This Research is about art of Pandanus webbing that comes as tradition art of Paninggahan at Junjung Sirih sub-district in Solok regency that has been existed since the ancestors. However, its existence is near from extinction nowadays. This research aims to analyze the existence and the development of Paninggahan pandanus webbing and also the products form, patterns, and the procedure of Pandanus webbing of Paninggahan. The method used in this research is descriptive qualitative. Data collection techniques in the form of observation, interviews, and documentation studies. Data analysis techniques that are in accordance with this research are data reduction, data presentation, and drawing conclusions. The result of this research showed that the existence of Paninggahan pandanus webbing is near from extinction, in the process of pandanus becomes staple, colouring process at mansiang, and the tools used in producing the webbing is still traditional. The early product of pandanus webbing is mat/ lapiak. The basic technique of webbing is crossed technique in which one move up and presses other, two move up and press other and so on based on the pattern. The webbing of pandanus is a symbol of Paninggahan women that has occurred since Paninggahan ancestors. its an obligaton to all womans of Paninggahan to do the art of Pandanus webbing as acknowledgement as woman of Paninggahan.